2010
DOI: 10.1590/s1516-14392010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage times on bond strength of resin cements to root canal

Abstract: The resin cements are responsible to retention of the indirect materials decreasing marginal leakage, increasing failure resistance compared with conventional cementation. The cementation within root canal is very hard due unfavorable conditions regarding the application of adhesive techniques caused by inadequate access. Therefore, considering the possibility to decrease steps of cementation, this study was performed to evaluate the bond strength of self-adhesive resin cement (RelyX TM U100, 3M ESPE) and resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…To compare the ability of different light guide tips coupled to an LED to cure dental composite material, suitable tests had to be chosen. Although many methods for testing the physical properties of dental composites are known, most are orientated towards comparing the properties of the different materials rather than the LCUs [35][36][37]. Compressive strength tests have previously been used to compare different LCUs but specifically in the present study this test was employed to compare different light guide tips [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…To compare the ability of different light guide tips coupled to an LED to cure dental composite material, suitable tests had to be chosen. Although many methods for testing the physical properties of dental composites are known, most are orientated towards comparing the properties of the different materials rather than the LCUs [35][36][37]. Compressive strength tests have previously been used to compare different LCUs but specifically in the present study this test was employed to compare different light guide tips [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The self-adhesive resin cement was chosen for luting of onlay planned because it does not require pretreatment of the dental substrate, reducing postoperative sensitivity and simplifying the cementation procedure. [17][18][19][20] Also it is verified that self-adhesive luting agents seem to successfully bond to dentin-restricted as well as to enamel-restricted cavities, predicting good clinical performance. 21 Some studies 22,23 reveal that self-adhesive resin cement has shown a acceptable clinical behavior.…”
Section: Discussionmentioning
confidence: 86%